Mobilizing Social and Organizational Resources in Project Type Cooperation: A Case Study in Networking in Interactive Media Firms - Makó, Csaba; Csizmadia, Péter (Competitio, 2005)
The paper aims at the identification and interpretation of specific coordination problems faced by project-based work organisations using the example of an interactive portal development for a leadingHungarian economic weakly. The study provides a brief overview of the most important theoretical approaches concerning project-based work organisations and the characteristics of the new or interactivemedia sector, which may act as a new model in the fast growing knowledge economy. The interactive portal development is typical of the so-called studio-model of project-based firms (PBF) characterised bythe novel and singular character of the product or service and by the uncertain and fluid nature of the necessary knowledge and skills. The study calls attention to the project manager’s key role in combiningformal and tacit skills and in the coordination of actors’ behaviour which is driven by different logics. In addition, the authors stress the importance of the client’s key role in designing and developing theinteractive media service.JEL classifications: L86; M54; Z13